Equine Parvovirus-Hepatitis in China: Characterization of Its Genetic Diversity and Evidence for Natural Recombination Events Between the Chinese and American Strains - Lu, Gang; Wu, Liyan; Ou, Jiajun; Li, Shoujun (Frontiers in Veterinary Science, 2020)
Equine parvovirus-hepatitis (EqPV-H) was first reported in a horse that died of equine serum hepatitis in the USA in 2018, and was determined having a strong association with equine serum hepatitis in the following studies. As a newly discovered virus, the genomic sequences of only seven EqPV-H strains have been reported. Considering this, an epidemiological study was performed to investigate the prevalence of EqPV-H in equines in Guangdong Province in China, and obtain genomic sequences of the field prevalent EqPV-H strains. The detection rate of EqPV-H was finally determined to be 8.33% (95% CI: 2.8%–18.4%), and EqPV-H’s coinfection with equine hepacivirus and equine pegivirus was also determined. Then, the genomes of the Chinese field EqPV-H strains were obtained by PCR, sequencing, and assembly. Through bootscanning analysis, Simplot analysis, and phylogenetic analysis, strong evidence for natural recombination events were found in two Chinese field EqPV-H strains. The natural recombination events occurred between the Chinese and American strains, and were determined within VP protein. Finally, the genetic distance of EqPV-H strains was investigated. Nucleotide identities of 97.1%-99.9% and 95.2%-100% were found for NS and VP between EqPV-H strains, respectively. Together with other molecular evidence obtained in the present study, the genetic diversity of EqPV-H was determined. Taken together, the results of the present study expand our knowledge on the epidemiological characteristics, genetic variability, and evolution of EqPV-H.